Gelatin as green adhesive for the preparation of a multifunctional biobased cryogel derived from bamboo industrial waste - Ding, Xiaoliang; Dai, Rui; Chen, Hui; Shan, Zhihua (Carbohydrate polymers, 2021)
•A green method to convert bamboo industrial waste into cryogel has been developed.•Bamboo fibres can improve the mechanical performance and thermal stability.•BFs/G cryogels exhibited excellent thermal-sound insulation performance.•BFs/G cryogels is a promising candidate for oil-spill cleaning applications. The effective utilization of bamboo industrial waste to produce value-added products is an important subject. In this paper, a multifunctional biobased cryogel derived from bamboo industrial waste was successfully developed. Bamboo fibres were first extracted from bamboo industrial waste and then dispersed in the gelatin solution to produce bamboo fibres/gelatin cryogels (BFs/G cryogels) by a freeze-drying process. The hydrophobicities of BFs/G cryogels were further improved by modification with methyltrichlorosilane. The prepared BFs/G cryogels possessed low density (23.9–29.5 mg/cm3), high porosity (90.41–95.85%), low thermal conductivity (0.031‒0.047 W/m·K) and excellent sound-insulating performance. The presence of rigid bamboo fibres improved the mechanical performance of the BFs/G cryogel. Furthermore, the BFs/G cryogels exhibited high oil absorption capacities of 23–66 times that of their dry weights. The successful development of this cryogel provides a path for the efficient utilization of bamboo industrial waste as a renewable biomass resource.